Analisis Peran Jaksa Pengacara Negara pada Sengketa Ekonomi Digital - Luciana, Luciana; Yulianingsih, Sri; Kossay, Methodius (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The rapid growth of the digital economy has transformed the landscape of legal disputes, particularly in Indonesia, where e-commerce transactions continue to increase significantly. This study examines the role of the State Attorney (Jaksa Pengacara Negara/JPN) in handling digital economic disputes, which remain limited despite the normative authority granted by law. Using a juridical-empirical approach, the research combines document analysis, in-depth interviews with prosecutors, judges, consumer protection officials, and digital law experts, and observation of selected cases. The findings reveal that JPN’s involvement remains concentrated on conventional disputes, such as breaches of electronic contracts and online fraud. In contrast, their role in strategic issues such as data protection and digital monopoly remains negligible. Comparative analysis with other jurisdictions highlights that prosecutors in the United States, the European Union, and Singapore have adopted more proactive and efficient roles in protecting public interests in the digital domain. The study concludes that the gap between JPN’s normative authority and its practical implementation reflects weaknesses in technical capacity, regulatory framework, and inter-institutional coordination. This research contributes to academic discourse by providing empirical and comparative insights into JPN’s role in digital disputes and by offering practical recommendations to strengthen its function through regulatory reform, capacity building, and institutional synergy. Strengthening JPN’s role is not only necessary to protect consumers and ensure legal certainty but also essential to enhance Indonesia’s legal competitiveness in the global digital economy.